Increasing Papaya Seed Viability By Osmoconditioning Treatment With Polyethylene Glycol (PEG) 6000 - Khairil Anwar Tanjung; Ade Fitriadi (INFOKUM, 2025)
Papaya (Carica papaya L.) is a plant that has high economic value, although its distribution is limited. One of the obstacles in increasing papaya production is the limited availability of seeds caused by a decrease in seed quality due to less than optimal storage. Seed viability is thought to be able to be increased through osmoconditioning techniques using Polyethylene Glycol (PEG) 6000. This study aims to evaluate the effect of osmoconditioning with PEG 6000 on the viability of papaya seeds (Carica papaya L.). The experimental design used was a Randomized Block Design with two treatment factors repeated three times. The first factor is the concentration of PEG 6000 consisting of 0%, 2%, 4%, and 6%. The second factor is the soaking time, which is 4 hours, 8 hours, and 12 hours. The results showed that osmoconditioning treatment with PEG 6000 had a significant effect on the viability of Papaya seeds (Carica papaya L.). The most effective concentration of PEG 6000 is 4%, while the optimal soaking time is 6 hours.